Evaluation of the Safety of Percutaneous Dilational Tracheostomy Compared with Surgical Tracheostomy in the Intensive Care Unit - Yuta Suzuki; Takeshi Suzuki; Yuko Yamamoto; Ayano Teshigawara; Jun Okuda; Tomohiro Suhara; Tomomi Ueda; Hiromasa Nagata; Takashige Yamada; Hiroshi Morisaki (Critical Care Research and Practice)
Background. Tracheostomy is a necessary procedure for patients who require long-term mechanical ventilation support. There are two methods for tracheostomy in current use: surgical tracheostomy (ST) and percutaneous dilational tracheostomy (PDT). In the current study, we retrospectively compared the safety of both procedures performed in our intensive care unit (ICU). Methods. In this study, we enrolled subjects who underwent tracheostomy in our ICU between January 2012 and March 2016. We excluded subjects who were <20 years old and underwent tracheostomy in the operating room. As a primary outcome, we evaluated the rate of complications between ST and PDT groups. The length of ICU stay, time to tracheostomy from intubation, and the rate of mechanical ventilation and mortality at 28 postoperative days were also examined as secondary outcomes. Results. Compared with the ST group, the rate of all complications was lower in the PDT group (13.4% vs. 38.8%, p=0.007). Although the rate of intraoperative complications did not differ between the two groups (3.8% vs. 8.1%, p=0.62), relative to the ST procedure, the PDT procedure was associated with fewer postoperative complications (34.6% vs. 9.6%, p=0.003). Among postoperative complications, accidental removal of the tracheostomy tube and an air leak from the tracheostomy fistula were less frequent in the PDT group than the ST group. Between the two groups, there were no significant differences in their secondary outcomes. Conclusion. This retrospective study indicates that relative to ST, PDT is a safer procedure to be performed in the ICU. Fewer postoperative complications following PDT might be attributed to the small skin incision made during this procedure.